Could actions improve retrieval performance in 4-to 6-year-old children? - Yang, Jing; Wang, Lijuan (European journal of developmental psychology, 2021)
It has been well documented in adults that compared to verbal learning, learning while the subject performs an action is far more effective. However, the results of previous studies involving children have not reached a consensus. The present study examined the action memory of 4- to 6-year-old children under various encoding conditions (i.e., VTs, EPTs and SPTs) using various retrieval tests (i.e., free recall, cued recall and recognition) to investigate the age-related development and enactment effect in action memory of 4- to 6-year-old children. The results demonstrated that the developmental differences in free recall memory performances under all encoding conditions across children aged 4 to 6 years reached significance. Additionally, cued recall and recognition performances under enacted-encoding conditions (both SPTs and EPTs) were better than those under verbal-encoding condition at all ages. Interestingly, the free recall performance under EPTs was superior to that under SPTs at all ages. Altogether, our findings showed that age-related development and enactment effects of action memory existed in children aged 4 to 6 years, depending on the test modalities, which require different mental resources.